2017
DOI: 10.3382/ps/pex140
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of meat and bone traits of Plymouth Rock cockerels and capons (P55) at different age

Abstract: The aim of the study was the comparison of Plymouth Rock cockerels and capons and the evaluation of the influence of their age on slaughter yield, meat quality, and bone traits. The studies were conducted on cockerels and capons from P55 strain (Plymouth Rock). At 16, 18, and 20 wk of rearing, a dissection of whole carcasses of cockerels and capons was conducted, and breast and leg muscles were evaluated in terms of the physical and chemical traits, as well as the chemical composition. Also, traits of femur an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
2
3
0
1
Order By: Relevance
“…Moreover, the results of our experiment and previous studies demonstrated that bending moment M of bone decreased after caponization 30 , 53 . Research conducted on birds bred until the 16th, 18th and 20th week of age, showed that there were no differences between cocks and capons in terms of yield strain ε y of tibia bone in all tested age groups of animals 60 , which is consistent with the results of our study. However, in another experimental trial 30 an increase in the yield strain of femur and tibia bone of capons compared to cockerels were shown.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the results of our experiment and previous studies demonstrated that bending moment M of bone decreased after caponization 30 , 53 . Research conducted on birds bred until the 16th, 18th and 20th week of age, showed that there were no differences between cocks and capons in terms of yield strain ε y of tibia bone in all tested age groups of animals 60 , which is consistent with the results of our study. However, in another experimental trial 30 an increase in the yield strain of femur and tibia bone of capons compared to cockerels were shown.…”
Section: Discussionsupporting
confidence: 92%
“…Muszyński et al 30 found no effect of caponization on the value of this parameter for both tibia and femur. Also, Kuźniacka et al 60 did not demonstrate the effect of castration on ultimate load of the tibia and femur of 16-, 18- and 20-week-old Plymouth Rock birds. In contrast, Tomaszewska et al 54 observed a reduced value of the ultimate strength of the femur of 24-week-old capons of Greenleg Partridge compared to cockerels of the same breed and age.…”
Section: Discussionmentioning
confidence: 92%
“…The cockerels of the layer line or dual-purpose breeds are another suitable option. Moreover, caponisation is beneficial in these breeds, because the caponisation can increase the culinary quality of the meat [4,5] and bone strength [6] compared to cockerels. One-day-old male layers are usually culled directly after hatching due to their inefficient growth rate compared with broilers, which implies a long fattening period and unfavourable feed conversion [7].…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, generally native and locally adapted breeds of hens are recommenced for alternative housing, as they are adapted to using the pasture and are less susceptible to unfavourable weather. These breeds are used for organic systems (Sosnówka-Czajka et al, 2017) and for production of capons (Calik et al, 2017) and poulardes (Obrzut et al, 2018;Krawczyk et al, 2019), high-quality, exclusive niche products (Kuźniacka et al, 2017). Hence, there is a need for studies on the bone quality in native and locally adapted breeds of hens, not only because of animal welfare but also because of the food safety (bone fragments in meat) and economic losses.…”
mentioning
confidence: 99%